Ta có: [TEX]\frac{1}{x}+\frac{1}{y}+\frac{1}{z} =0 [/TEX]
\Rightarrow [TEX]\frac{1}{y}+\frac{1}{z} = -\frac{1}{x}[/TEX]
\Rightarrow [TEX]N=\frac{yz}{x^2} + \frac{xz}{y^2} + \frac{xy}{z^2}[/TEX]
[TEX]N= xyz(\frac{1}{y^3}+\frac{1}{z^3}) + \frac{yz}{x^2}[/TEX]
[TEX]N= xyz.(\frac{1}{y}+\frac{1}{z}).(\frac{1}{y^2}+\frac{1}{z^2}-\frac{1}{yz}) + \frac{yz}{x^2}[/TEX]
[TEX]N= xyz.(-\frac{1}{x}).[(\frac{1}{y}+\frac{1}{z})^2 -\frac{3}{yz} ) +\frac{yz}{x^2}[/TEX]
[TEX]N= -yz.(\frac{1}{x^2}-\frac{3}{yz}) + \frac{yz}{x^2}[/TEX]
[TEX]N= -\frac{yz}{x^2} + 3 + \frac{yz}{x^2}[/TEX]
[TEX]N=3[/FONT][/TEX]